Persediaan Fasilitas Pelayanan Sisi Darat Pada Terminal (1A) Bandara Soekarno Hatta - Welly Pakan (WARTA ARDHIA, 2010)
The airport is the gateway to the national economy and international events and place over the mode of transportation, operations occur in a variety of interactions between the main components namely: Airport Manager, airline operators, and service user.Along with the increasing frequency of flights and the use of various types of aircraft will require reliability of the facilities at airports in order to support aviation safety and to ensure the security and comfort for users of airport services. One of the facility of the airport is directly related to passenger is land side facilities services.